THE CHALLENGES OF EJA TEACHERS: RESIGNIFYING TEACHING PRACTICE IN THE TEACHING OF EJA - Janisara Araújo Sales, Rosa; da Silva Souza, Cleiciane; Serlir Silva Sousa, Antônia; Jane Araújo Sales, Jussara; da Silva Oliveira, Márcio (Revista Gênero e Interdisciplinaridade, 2024)
The present work aimed to report the experiences of teachers working at EJA in a school in the municipal network of Boa Vista, Roraima. The need to understand the challenges and practices of teaching methodologies in EJA was addressed. The methodology used was content analysis. The results revealed three categories: Category 1 - Training; Category 2 - Challenges; Category 3 - affectivity, which evidenced the way EJA teachers understand the teaching/learning issues of these students. The investigation pointed out that the lack of implementation of public and educational policies represented by the categories analyzed requires a change of paradigms, as well as physical structure, pedagogical/didactic and human resources. In addition to the issue of teacher training to deal with learning difficulties of EJA students. It is concluded that the pedagogical practices that serve both young and adults need to be renewed, but always considering their prior knowledge for more significant learning.